2021
DOI: 10.2147/ndt.s251547
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy and Clinical Effectiveness of EEG Neurofeedback as a Personalized and Multimodal Treatment in ADHD: A Critical Review

Abstract: Purpose Recent reviews have proposed that scientifically validated standard EEG neurofeedback (NF) protocols are an efficacious and specific treatment for attention-deficit hyperactivity disorder (ADHD). Here, we review the current evidence for the treatment efficacy and clinical effectiveness of NF in ADHD to investigate whether NF treatment personalization (standard protocols matched to the electrophysiological features of ADHD) and combination with other interventions (psychosocial, sleep hygie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…However, so far evidence suggests that fMRI-NF learning can be achieved in relatively fewer sessions than EEG-NF [96] . For ADHD, EEG-NF typically requires 25-40 sessions of 45-60 min (Arns et al, 2009), and full treatment costs for 30-40 sessions have been estimated at USD4000-6000, similar to pharmacotherapy over 5-10 years [201] (Garcia Pimenta et al, 2021). This means higher costs for the administering therapist as opposed to fMRI-NF, which requires fewer sessions.…”
Section: Overall Conclusionmentioning
confidence: 99%
“…However, so far evidence suggests that fMRI-NF learning can be achieved in relatively fewer sessions than EEG-NF [96] . For ADHD, EEG-NF typically requires 25-40 sessions of 45-60 min (Arns et al, 2009), and full treatment costs for 30-40 sessions have been estimated at USD4000-6000, similar to pharmacotherapy over 5-10 years [201] (Garcia Pimenta et al, 2021). This means higher costs for the administering therapist as opposed to fMRI-NF, which requires fewer sessions.…”
Section: Overall Conclusionmentioning
confidence: 99%
“…While priming protocols lack some consistency and are not yet ready to be implemented on final products like SR serious games, they potentially provide an essential layer of personalization and mutual game-player adaptation. Actually, a review of attention-deficit hyperactivity disorder (ADHD) randomized control trials indicated that the long-term effects of personalized NF interventions were superior to non-personalized NF [97]. To optimize self-regulation learning, future work will also address the use of neural networks to learn the sequence of stimuli that leads the subject towards their personalized "optimal" state (e.g., using reinforcement learning, deep learning for time series forecasting with long short-term memory networks, multilayer perceptron's, convolutional neural networks, between others).…”
Section: General Discussion and Future Proposalsmentioning
confidence: 99%
“…In their review the authors further discussed heightened reward sensitivity in children diagnosed with ADHD as a non-specific factor contributing to the training effect on clinical outcomes (Garcia Pimenta et al, 2021). While neurofeedback applications in clinical populations have focused on restoring cognitive and behavioral functionality, studies with non-clinical samples have concentrated on enhancing cognitive performance.…”
Section: Introductionmentioning
confidence: 99%